The effect povidone-iodine on the wound healing process: A study on fibroblast populated collagen lattice (FPCL) model - Arief Budiyanto, Widodo Wirohadidjojo, Retno Danarti, Suswardana, (Universitas Gadjah Mada, 2014)
Povidone-iodine (PI) 10% solution is an effective antiseptic. However, it appears to be toxic tothe cells involved in wound healing. The aim of this study is to evaluate the toxicity of PI oncultured human fibroblast using fibroblast populated collagen lattice (FPCL) model. The culturedhuman fibroblast was divided into 6 groups i.e. 5 groups were exposed by PI 1, 0.1, 0.01, 0.001and 0.0001%, and 1 group was exposed by phosphate-buffered-saline (PBS). Twenty-four hourslater, the media was washed using PBS. The size of the FPCL media on each group wasobserved over time by serial photographs, which then were measured by Image-J computerprogram. Exposure of 0.1, 0.01, 0.001 and 0.0001 PI caused an obvious reduction of fibroblastâscontraction capability on FPCL media, which described temporary fibroblast injury, that showinga concentration-dependent recovery phenomenon after 48th hour. Furthermore, 1% PI exposureleads to a permanent fibroblast injury. In conclusion, PI exposure in concentration more than0.1% has a permanent toxic effect on fibroblast that clearly observed using a simple FPCLmodel.